Between happiness and sorrow: Phenomenal characteristics of autobiographical memories concerning war episodes and positive events in the Gaza Strip. (December 2020) - Manzanero, Antonio L; Fernández, Juan; Gómez-Gutiérrez, María del Mar; Álvarez, Miguel A; El-Astal, Sofián; Hemaid, Fairouz; Veronese, Guido
In the present study, we investigated the characteristics of memories concerning both traumatic events (war-related memories) and positive life events (happy memories) in a group of Palestinian students who were victims of war and military violence. An ad hoc questionnaire was developed to explore differences in how the traumatic and happy events were recalled, both in relation to the actual events experienced and in relation to their phenomenological features in autobiographical memory. Traumatic memories were observed to be richer in sensory characteristics, more vivid, and generally more detailed; the emotions associated with traumatic episodes were more intense and played a key role in recall, as did recurrent thoughts and discussion of events and post-event autobiographical memories. In sum, traumatic memories are more complex than non-traumatic ones given their more sensory and analogical nature, which can also undermine accuracy of recall. The clinical implications of these findings and possible directions for future research are discussed.